(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
In this study, the germination rate of Trigonella foenum-graecum L. (Greek shambala) seeds in the field was studied under different sowing dates and agroclimatic conditions. Based on the results obtained from several sowing dates in 2023/2024, the germination efficiency of seeds was found to be related to factors such as air temperature, soil temperature and relative humidity. The conditions in March and September were the most favorable, and germination rates were moderate to high. These results confirm that March and September are the most suitable times for sowing T. foenum-graecum seeds. However, low temperatures in April and November limited germination and led to low efficiency. The results of the study will help determine the most suitable sowing times for T. foenum-graecum in the field.